2016
DOI: 10.1080/15548627.2016.1235125
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic G protein-coupled receptors control cell migration by repressing autophagosome biogenesis

Abstract: Chemotactic migration is a fundamental behavior of cells and its regulation is particularly relevant in physiological processes such as organogenesis and angiogenesis, as well as in pathological processes such as tumor metastasis. The majority of chemotactic stimuli activate cell surface receptors that belong to the G protein-coupled receptor (GPCR) superfamily. Although the autophagy machinery has been shown to play a role in cell migration, its mode of regulation by chemotactic GPCRs remains largely unexplor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 86 publications
2
28
0
Order By: Relevance
“…Two approaches of autophagy inhibition were compared, namely blocking autophagosome formation versus blocking autophagosome-lysosome fusion, by respectively targeting ATG5 and RAB21 expression through RNA interference, using previously validated siRNA 44,45 . RAB21 was selected given its ability to mediate the sorting of VAMP8 to endolysosomes 44 , the latter being required for autophagosome-lysosome fusion 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Two approaches of autophagy inhibition were compared, namely blocking autophagosome formation versus blocking autophagosome-lysosome fusion, by respectively targeting ATG5 and RAB21 expression through RNA interference, using previously validated siRNA 44,45 . RAB21 was selected given its ability to mediate the sorting of VAMP8 to endolysosomes 44 , the latter being required for autophagosome-lysosome fusion 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, GPCRs like the adenosine A2 receptor regulate autophagosome biogenesis in order to inhibit neutrophil apoptosis. Similarly, the urotensin receptor UTS2R and CXCR4 suppress the biogenesis of autophagosomes, a process critical for cell migration. These studies highlight the importance of autophagosomes in the regulation of GPCRs, and the connections between GPCR signaling and the control of autophagosome formation.…”
Section: Alternative Destinations For Gpcrs—autophagy Exosome Packagmentioning
confidence: 99%
“…Coly et al identified that the novel effects of two chemotactic GPCRs, C‐X‐C motif chemokine receptor (CXCR4) and urotensin 2 receptor, on repressing autophagy rely on CAPN/CAPN activation. The antiautophagic function of CAPN is probably because of the cleavage of several key elements in the formation of pre‐autophagosomal vesicles from the plasma membrane (PM), including the clathrin adaptors phosphatidylinositol binding clathrin assembly protein (PICALM), activator protein‐2 (AP2) complex, and autophagy‐related protein (ATG7; Coly et al, ). In addition, the altered expression of CXCR3, which comprises two splice variants, CXCR3A and CXCR3B, in prostate cancer cells is capable of regulating cell migration and invasion.…”
Section: Correlating Signaling Pathwaysmentioning
confidence: 99%